Proceedings of the ANSO-PAS-QAU Workshop 2023 on “Ensuring Biosafety: Empowering Trainers in Risk Management and Biosecurity” - Huma Gul; Naveera Khan; Muntasa Usman; Sidra Rahman; Irum Iqrar; Zabta Khan Shinwari; Muhammad Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Three days workshop entitled “Ensuring Biosafety: Empowering Trainers in Risk Management and Biosecurity,” (August 12-14, 2023) was organized at Bara Gali Campus, University of Peshawar. The workshop consisted of practical lessons on biosafety in the lab and during fieldwork, risk assessment techniques, biosecurity practices, experiment design, and execution. In addition, risk management, policy-making, and the rising concerns of antibiotic resistance were also discussed by keynote speakers and trainers. The course included theoretical lectures and hands-on exercises, allowing attendees to put their newfound knowledge to use in realistic situations. A field excursion also highlighted several plant types and aspects related to handling possibly toxic plants. In summary, the event stresses the importance of having a thorough familiarity with biosafety and risk management while practicing laboratory procedures.